SUN-LB091 Impact of Albumin Corrected Calcium on the Prevalence and Categories of Hypercalcemia in Hospitalized Patients - Balasubramanian, Priyadarshini (J Endocr Soc, 2019)
Introduction: Hypercalcemia is a common clinical problem encountered in hospitalized patients. Mild to moderate hypercalcemia diagnoses may be missed during hospitalization since albumin corrected calcium is not automated with laboratory results. Methods: We performed a retrospective study using total and albumin corrected calcium to identify the prevalence and causes of hypercalcemia in hospitalized patients. Patients with corrected calcium ≥ 10.5 mg/dL were identified by searching the electronic medical records of hospital, from June 2012 to June 2017. Albumin-corrected calcium was calculated with the formula [((4-albumin concentration in g/dl) * 0.8) + Total serum calcium in mg/dl] and data were analyzed using SPSS software. Results: From June 2012 to June 2017 there were 97,900 hospital admissions and 711 cases of hypercalcemia based on total calcium, and 1,067 cases based on corrected calcium, resulting in prevalence rates of 0.73% and 1.09%, respectively. Of the 1067 patients, 86% of patients had mild hypercalcemia (10.5-11.9 mg/dL), 10% had moderate hypercalcemia (12-14 mg/dL) and 4% had severe hypercalcemia (>14 mg/dL). When total calcium was considered, malignancy and hyperparathyroidism accounted for the majority of cases representing 48.2% and 28.6% of cases, respectively, followed by the category of other causes (13.2%). When corrected calcium was used the most common categories of hypercalcemia were malignancy (35.4%), hypercalcemia that was not further evaluated (31.1%), and hyperparathyroidism (22.4%). The overall effect of using corrected calcium was a decrease in the proportion of hypercalcemia cases due to malignancy and hyperparathyroidism from 48.2% to 35.4%, and from 28.6 % to 22.4 %, respectively, but an increase in the proportion of unidentified cases from 10% to 31.1%. 31.1% of patients with hypercalcemia were not further evaluated and no identifiable cause was available, resulting in unexplained hypercalcemia being the second most common category. Overall, the majority of hypercalcemia cases were non-malignant. Conclusion: Our major findings are that the use of albumin corrected calcium resulted in a 49% increase in detection of hypercalcemia cases and that the majority of hypercalcemia cases in hospitalized patients are not associated with malignancy. We suggest that increasing the detection of hypercalcemic disorders by correcting for low albumin is worthwhile in order to achieve better estimates of disease prevalence and to detect potentially deleterious conditions in their earlier stages. We propose the implementation of auto calculated albumin corrected calcium to be displayed with routine laboratory results to increase detection of hypercalcemia cases that may be overlooked due to hypoalbuminemia in hospitalized patients. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.